The Patent Landscape of BRAF Target and KRAS Target - Zhang, Hai-Long; Li, Yongxia (Recent Patents on Anti-Cancer Drug Discovery, 2023)
Background: KRAS and BRAF targets are involved in the epidermal growth factor receptor pathway. KRAS and BRAF targets are the most frequent driver mutations in cancer. Objective: The objective of the study was to present the recent developments in the KRAS target and the BRAF target. Methods: KRAS target and BRAF target were analyzed by US patent analysis. All US granted patent documents from January 2002 to November 2021 were retrieved. Results: The results showed both KRAS and BRAF targets to be attractive targets for developing anticancer drugs. The technology of RNA interference has been developed for drug discovery related to the KRAS target. Our study indicates that the structural screening of inhibitors between the KRAS target and the BRAF target should be an inverse option. Conclusion: The chemical structures of inhibitors of BRAF target exhibited a unique classification of C07D405. The inhibitors of BRAF target could be used for the treatment of various cancers. However, the inhibitors of KRAS target did not show this feature. The present study provides new insight into drug discovery involving KRAS and BRAF targets.
Keywords: targeted drugs